Quantifying nearshore bathymetric change using an Unoccupied Surface Vehicle equipped with RTK-GNSS and echosounder: A case study in the Neuse River Estuary, NC - Knowles, Ryann (East Carolina University, 2022)
The Neuse River Estuary (NRE) located in eastern North Carolina is experiencing shoreline bluff retreat and corresponding nearshore bathymetric change due to an increase in intense storm events such as hurricanes. Monitoring changes in nearshore bathymetry can aid in understanding sediment flux for management and restoration purposes. New remote sensing devices such as small Unoccupied Surface Vehicles (sUSV) allow for on-demand repeat bathymetric surveys of shallow nearshore environments where larger vessels cannot reach. This study uses a sUSV equipped with a single beam echosounder to investigate nearshore morphological changes in the Neuse River Estuary. Two Real-time Kinematic Global Navigation Satellite Systems (RTK-GNSS) and sUSV surveys were carried out in February and April 2022. For each of the two surveys, three Bathymetric Elevation Models (BEMs) were generated using Empirical Bayesian Kriging (EBK), Global Polynomial Interpolation (GPI), and Spline. EBK achieved the best result for both surveys based on conditions observed in the field as well as a vertical Root Mean Square Error (RMSE) of 0.21 m for February and 0.16 m for April. Wave and weather sensors were installed for this study to help determine potential causes of morphological changes. While both months had similar average wind speeds (average 5-10 m/s), their directions were different (Northeast and South directions for February and Southwest direction for April). As can be expected in a wave dominated estuary with these observed wind speeds, 90th percentile wave depth minimum and maximum ranged 0.05 m February and 0.03 m for April. Short term changes in the nearshore bathymetry were negative resulting in erosion with no estimated deposition. Bathymetry loss ranged from 0.3 to 0.69 m between February and April, and the observed wind and wave data indicate these changes were likely due to another contributing factor such as currents. ¬¬¬To assist future work using sUSVs in shallow nearshore estuarine environments, a workflow of best practices when conducting sUSV surveys was developed in this study. It is anticipated that the results from this study will useful information for researchers conducting sUSV surveys as well as the causes of nearshore morphological change in shallow estuarine environments.
Keywords: sUSV, RTK-GNSS, EchoBoat, Nearshore, Environment